Penanaman Perilaku Agama Islam Pada Anak Tuna Laras pada Sekolah Inklusi - Alfi Zidanurrohim; Difa Ul Husna; Rifaah Salwa Albana; Wahyu Lestari; Utut Abdilah Iskandar (JIE (Journal of Islamic Education), 2023)
The discussion this time is about guidance in Islamic education for children with special needs for the disabled. This needs to be discussed because every individual is obliged and has the right to get education, especially education related to Islam. The method used by the library is with a qualitative approach, we collect several literature studies by taking the form of books, scientific articles and theses as basic research materials. The role and characteristics and learning model must be applied, adjusted to the needs and curriculum of each educational institution, with the role of Islamic education in guiding students with special needs, that is, through Islamic education, efforts are made to instill Islamic values in order to prepare a generation of noble character. Characteristics of children with special needs for hearing impairment include not being able to properly define mental health and normal behavior, not being able to measure their own emotions and behavior and experiencing difficulties in carrying out socialization functions so that a relevant guidance model is needed to deal with these conditions. Therefore education is an absolute right for anyone, children with hearing impairments must also be given the same education as children in general, even though with different methods. These are the uses and benefits of SBL institutions that are able to provide services for disabled children.